Endodontic Care for Patients with Polycythemia: Clinical Considerations and Case Analysis - Nugroho, Dian Lestari Putri; Nugraheni, Tunjung; Imandini, Aldila; Rinastiti, Margareta (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Polycythemia is a myeloproliferative neoplasm characterized by uncontrolled proliferation of red blood cells due to mutations in early hematopoietic cells, often linked to Janus kinase 2 (JAK2) gene mutations. Polycythemia vera (PV), the primary form of the disease, leads to increased blood viscosity and stasis, raising the risk of thrombotic events such as stroke and myocardial infarction. Secondary polycythemia results from hypoxic conditions, stimulating erythropoietin production. Diagnosis is confirmed through hemoglobin and hematocrit levels, with treatment aimed at reducing thrombosis and hemorrhage risks. Low-risk patients are treated with aspirin and phlebotomy, while high-risk cases may require cytoreductive therapies like hydroxyurea.In our case, a patient presented with necrosis and horizontal bone loss in tooth 36, complicated by polycythemia. Due to the increased risk of bleeding and inflammation, the decision was made to prioritize endodontic treatment, avoiding periodontal surgery. The patient, considered low-risk for PV complications due to the absence of thrombosis history, was managed conservatively. Preoperative coordination with hematologists was essential to optimize hematologic parameters and minimize potential risks.The goal of endodontic treatment was to disinfect and seal the root canal, reducing inflammation in the surrounding periodontal tissues and preventing reinfection. This approach allowed for effective management of the patient's oral condition while minimizing systemic risks. This case highlights the importance of a multidisciplinary approach in managing dental treatment for patients with polycythemia, ensuring both local and systemic complications are effectively addressed.